Tingkat Kognitif, Afektif dan Konatif Masyarakat Banjarmasin dalam Membeli Secara Online Berdasarkan Demografis - Teguh Wicaksono; Syahrani Syahrani; Khalisa Rahmina Suryani (Politeknik Negeri Bengkalis, 2020)
Online buying is a new method of buying and selling using internet as the media of transactions. It is believed that it could shift the conventional transactions, which is still the characteristic of Banjarmasin’s people. This study aims to determine cognitive, affective and conative level of the people that live in Banjarmasin in online buying’s activity based on demographics. This study wants to find out if there is any differences in cognitive, affective and conative level of it as well as whether there is an influence of demographic factors to cognitive, affective and conative level of Banjarmasin's people in online buying. This is a survey research that uses questionaire as the research instrument, and 150 respondents are taken from people who live in Banjarmasin as sample. Data analysis techniques used; categorized variabel analysis to see the distribution of respondents by category; Chi Square test to see the differences of cognitive, affective and conative level based on demographics; Kruskal Wallis test to see the influence of demographic factors to cognitive, affective and conative level. Result of this study shows that cognitive, affective and conative level of Banjarmasin's people in online buying, majority is in medium category, it means majority of Banjarmasin's people know, understand and like to buy online; based on demographics, there is no differences of cognitive, affective and conative level of Banjarmasin's people in online buying; demographic factors do not influence the cognitive, affective and conative level of Banjarmasin's people in online buying.